Microneedle Dressing: Intelligent Silk Fibroin Based Microneedle Dressing (i‐SMD) (Adv. Funct. Mater. 3/2021). (18th January 2021) - Gao, Bingbing; Guo, Maoze; Lyu, Kai; Chu, Tianshu; He, Bingfang
Abstract : In article number 2006839, Bingbing Gao, Bingfang He, and co‐workers fabricate intelligent silk fibroin‐based microneedle dressing (i‐SMD) with photonic crystals, microfluidics. and microelectro circuits by simply duplicating negative molds. The intelligent and highly integrated i‐SMD with electro‐microfluidics and smart drug release systems enable sensitive biochemical and physiological sensing. It could also serve as an intelligent dressing for facilitating wound healing.